PENGARUH KEMANDIRIAN DAERAH, TINGKAT KETERGANTUNGAN, UKURAN PEMERINTAH DAERAH DAN TEMUAN AUDIT TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Badruddin Badruddin (LPPM STIE Lhokseumawe, 2019)
This study aims to examine the effect of regional independence, level of dependence, local government size and audit findings on the level of disclosure of financial statements of North Aceh District government. The data used in this research are 50 primary data with purposive sampling technique. The method used to analyze the independent variables with the dependent variable is the multiple linear regression method and the classical assumption test. The results of the research partially regional independence and dependency level have no effect on the level of disclosure of the financial statements of the North Aceh District Government, while the regional government variable size and audit findings have a significant effect on the level of disclosure of North Aceh District Government financial statements. Simultaneously it shows that, regional independence, the size of the regional government, the level of dependency and audit findings together have a significant effect on the disclosure of the financial statements of the North Aceh District Government.